The Effect of Evening Primrose and vitamin B6 on premenstrual syndrome: a randomized clinical trial - Arezoo Shayan; Hassan Ahmadinia; Seyedeh Zahra Masoumi; Fatemeh Shobeiri; Shirin Moradkhani; Hadis Sourinezhad (Mashhad University of Medical Sciences, 2019)
Introduction: Premenstrual syndrome is a set of physical and psychological symptoms which occur periodically during the secretory phase of the menstrual period. This study was performed with aim to compare the effect of Evening Primrose Capsule and vitamin B6 and placebo on the severity of premenstrual syndrome symptoms. Methods: This randomized double-blind clinical trial was conducted on 120 students with premenstrual syndrome at Hamadan University of Medical Sciences in 2016. The subjects were randomly divided into 3 groups of 40 cases and for two consecutive cycles, the first group received daily 2 tablets (40 mg) vitamin B6, the second group received evening primrose capsules (1000 mg) twice daily, and third group received daily 2 placebo, 14 days before menstruation up to 5 days after it. The severity of premenstrual syndrome symptoms was compared at the end of each cycle by daily status recording form. Data were analyzed by SPSS software (version 21) and Chi-square, ANOVA, paired t-test, and Tukey test. P<0.05 was considered statistically significant. Results: Before intervention, the mean severity of symptoms in the group receiving vitamin B6 was 62.54±22.17 and in the group receiving evening primrose capsules was 61.45±21.25 that after the intervention decreased to 54.08±18.15 and 21.38±9.05, respectively, but in the placebo group, the severity of the symptoms before the intervention was 61.21 ± 30.12 and the severity of the symptoms increased after the intervention (62.48 ± 19.17). The severity of premenstrual syndrome symptoms had significant decrease only in the group of evening primrose capsule (P <0.01). Conclusion: The evening primrose capsule significantly reduces the symptoms of premenstrual syndrome compared with vitamin B6 and placebo; therefore, due to the limited side effects observed, it can be useful in women with premenstrual syndrome